THE IMPACT OF ISLAMIC COUNSELING ON THE MENTAL HEALTH OF PRISONERS IN YOGYAKARTA CORRECTIONAL INSTITUTION - Pahlewi, Reza Mina (Srawung: Journal of Social Sciences and Humanities, 2024)
Prisoners’ mental health is an important issue in the correctional context. Various counseling methods have been used to improve the mental welfare of prisoners, one of which is Islamic counseling which is based on Islamic teachings. This research aims to examine the impact of Islamic counseling on the mental health of prisoners in the Yogyakarta Correctional Institution. This research uses a quantitative method with a quasi-experimental design. The research sample consisted of 60 randomly selected prisoners and was divided into two groups from the experimental group who received Islamic counseling and the control group who did not receive the intervention. Data were collected through a validated mental health questionnaire, and analyzed using t-test to determine whether there were differences before and after the intervention in the two groups. The results showed that there was a significant improvement in the mental health of prisoners who received Islamic counseling compared to the control group (p<0.05). Islamic counseling was effective in reducing the levels of stress, anxiety, and depression among the inmates. Islamic counseling has a positive impact on the mental health of prisoners in Yogyakarta Correctional Institution. The results of this research provide practical implications for correctional institution managers in developing faith-based counseling programs to improve the mental welfare of prisoners.